Dual catalyst system for selective vinyl chloride production via ethene oxychlorination. Issue 2 (2nd January 2020) - Scharfe, Matthias; Paunović, Vladimir; Mitchell, Sharon; Hauert, Roland; Xi, Shibo; Borgna, Armando; Pérez-Ramírez, Javier
Abstract : A dual system featuring ZrO2 -supported CeO2 and Ca-doped Al2 O3 catalysts enables the direct production of vinyl chloride via ethene oxychlorination. Abstract : A dual system comprising two catalytic reactors connected in series was developed for the direct conversion of ethene to vinyl chloride monomer (VCM). The first reactor uses ZrO2 -supported ceria (CeO2 /ZrO2 ) to perform ethene oxychlorination to 1, 2-dichloroethene (EDC) that is dehydrochlorinated to VCM in the second reactor over calcium-promoted γ-Al2 O3 . The choice of carrier for ceria is of critical importance to maximize the EDC production by reducing combustion products. While MgO, SiO2, SiC, TiO2, ZSM-5, and γ-Al2 O3 carriers induced higher overoxidation compared to bulk ceria, ZrO2 was the only carrier that suppressed CO x formation. Moreover, the latter carrier led to the highest oxychlorination activity. The unique performance of the CeO2 /ZrO2 catalyst was rationalized by its ability to promote chlorine evolution and to suppress the combustion of chlorinated products, as inferred from the activity evaluation in HCl and VCM oxidation, respectively. The outstanding redox properties, enabling operation at low temperature and thus high selectivity, are associated with the formation of defective CeO2 nanoparticles, contrasting the low activity over Ce–Zr mixed oxide. In order to subsequently form VCM, an efficient EDC dehydrochlorination catalyst was designed by moderating the acidity of γ-Al2 O3 via calcium doping and used in a reactor after CeO2 /ZrO2 . This dual catalyst system displayed 100% selectivity to VCM at 25% ethene conversion, surpassing the space time yield of the best ethene-to-VCM catalyst EuOCl by a factor of four, where the first step is operated at an elevated temperature of about 100–150 K with respect to cupric chloride benchmarks. In addition, the catalytic dehydrochlorination, operated at a lower temperature of 100 K than the current non-catalytic process, showed minimized coke formation. This developed system rendered stable after slight initial deactivation, offering promising potential to intensify VCM production.